Acacia erioloba: monograph and annotated bibliography - Barnes, R; Fagg, C; Milton, S (Oxford Forestry Institute, University of Oxford, 1997)
One of the most crucial environmental challenges in Africa is how to restore and increase the productivity of non-arable lands in the drier parts of the continent. Increasing population pressures coupled with periodic droughts have brought about deforestation in these areas and, without trees to protect and maintain soil fertility, annual grasses replace the more nutritious perennial species and most of the productive potential is lost. Many exotic tree species have been introduced in attempts to find a rapid solution to the problem but the success that these have had in the better watered parts has not been repeated in the semi-arid regions where the ravages of droughts, termites and browsing animals, among other hardships, have made it difficult for them to survive. It is now generally accepted that the solution lies in the management and cultivation of the indigenous trees, particularly the pioneer legumes that are the natural re-colonizers of disturbed land in these environments. Most prominent among these are the acacias which have the attributes required in this situation, including an ability to use nutrients and water from great depths, to fix nitrogen and to produce fuelwood and food for domestic stock...